Development of a novel wide-angle gamma-ray imaging air Cherenkov telescope with SiPM-based camera for the TAIGA hybrid installation - Chernov, D; Astapov, I; Bezyazeekov, P; Bonvech, E; Borodin, A; Brueckner, M; Budnev, N; Chernukh, D; Chiavassa, A; Dyachok, A; Fedorov, O; Gafarov, A; et al. (Journal of Instrumentation, 2020)
The TAIGA complex-detector is designed to study gamma and cosmic rays in the energy range above 30 TeV. We are developing a novel wide-angle imaging air Cherenkov telescope with a SiPM based camera with a field of view of 15-20 degrees and an aperture of around 1 m(2). In this report we present the design of the telescope imaging camera (optical and data acquisition systems), based on 1000-1200 SiPMs. The prototype of such camera, based on 49 SiPMs, is operating at the TAIGA's site in the Tunka valley since September 2019. The design of the prototype and the preliminary results of data analysis is presented.